Electrochemical Microwell Plate to Study Electroactive Microorganisms in Parallel and Real-Time - Kuchenbuch, Anne; Frank, Ronny; Ramos, José Vazquez; Jahnke, Heinz-Georg; Harnisch, Falk (Frontiers in Bioengineering and Biotechnology, 2022)
Microbial resource mining of electroactive microorganism (EAM) is currently methodically hampered due to unavailable electrochemical screening tools. Here, we introduce an electrochemical microwell plate (ec-MP) composed of a 96 electrochemical deepwell plate and a recently developed 96-channel multipotentiostat. Using the ec-MP we investigated the electrochemical and metabolic properties of the EAM models Shewanella oneidensis and Geobacter sulfurreducens with acetate and lactate as electron donor combined with an individual genetic analysis of each well. Electrochemical cultivation of pure cultures achieved maximum current densities (jmax) and coulombic efficiencies (CE) that were well in line with literature data. The co-cultivation of S. oneidensis and G. sulfurreducens led to an increased current density of jmax of 88.57±14.04 µA cm-2 (lactate) and jmax of 99.36±19.12 µA cm-2 (lactate and acetate). Further, a decreased time period of reaching jmax and biphasic current production was revealed and the microbial electrochemical performance could be linked to the shift in the relative abundance.